Biological functions of endophytic bacteria in Robinia pseudoacacia ‘Hongsen’ - Huang, Minqing; Chen, Lijing; Ma, Jiasi; Mo, Jingzhi; He, Lu; Liang, Qihua; Peng, Guixiang; Tan, Zhiyuan (Frontiers in Microbiology, 2023)
Endophytes and their host plants have co-evolved for a very long time. This relationship has led to the general recognition of endophytes as a particular class of microbial resources. This study examined microbial species and functional diversity in Robinia pseudoacacia 'Hongsen' using culture-dependent (isolation) and cultureindependent techniques. A total of 210 isolates were isolated from R. pseudoacacia 'Hongsen.' These isolates were clustered into 16 groups by the In Situ PCR (IS-PCR) fingerprinting patterns. 16S rRNA gene sequence analysis of the representative strain of each group revealed that these groups belonged to 16 species of 8 genera, demonstrating the diversity of endophytes in R. pseudoacacia 'Hongsen' .'Bacillus is the most prevalent genus among all the endophytic bacteria. High-throughput sequencing of endophytic bacteria from R. pseudoacacia 'Hongsen'of the plant and the rhizosphere soil bacteria showed that the bacterial populations of soil near the root, leaf, and rhizosphere differed significantly. The microbial abundance decreased in the endophytes as compared to the rhizosphere. We observed a similar community structure of roots and leaves. With and without root nodules, Mesorhizobium sp. werewas significantly different in R. pseudoacacia 'Hongsen.'plant. It was predicted that R. pseudoacacia 'Hongsen'plant endophytic bacteria would play a significant role in the metabolic process, such as carbohydrate metabolism, amino acid metabolism, membrane transport, and energy metabolism.